Comparing the Social Support Which Fathers and Mothers of Preterm Infants Receive in the Neonatal Intensive Care Units - Zahra Ahmadi; Mona Joz Mohtashami; Na`imeh Seyyed Fatemi; Hamid Haghani (Iran University of Medical Sciences, 2016)
Background: The birth of a preterm infant is a stressful experience for parents. The nurse's support for the family of such newborns seems to be important and necessary. This study aimed to examine the social support received by the fathers as compared with the mothers of preterm infants hospitalized in the neonatal intensive care unit (NICU). Methods: This was a comparative, descriptive study. The study population included all parents of preterm infants hospitalized in the NICUs of 3 educational treatment centers affiliated to Tehran University of Medical Sciences during the first 6 months of the year 2014. Study sample consisted of 130 couples selected through the convenient sampling method, and data collection tool was Tarkan et al. social support questionnaire. Then, the obtained data were analyzed using the Independent t test by SPSS version 20. Results: The results showed that the most social support with the mean(SD) score of 69.0(6.3) was received by the mothers, and 57.0(2.3) for fathers was emotional support and the least level of social support with the mean score of 80.0(3.3) for the mothers and 65.0(16.3) for fathers was tangible support, and mothers with mean score 65.0(52.3) as compared with fathers 56.0(21.3), received more support in all 3 aspects of social support, i.e. affirmative, tangible, and emotional. Conclusion: Our findings indicate that parents are desirous of more social support, especially with regard to the tangible support. Therefore, planning is required for promotion and creation of opportunities for the nurses to provide more supports to parents at NICUs, especially to fathers who usually receive less support. It is recommended that nurses improve their effective and mutual communication and interaction with parents.